Australian hospital staff perceptions of barriers and enablers of domestic and family violence screening and response - Debra K. Creedy; Kathleen Baird; Kerri Gillespie; Grace Brandjerdporn (BMC, 2021)
Abstract Background Hospital presentations provide unique opportunities to detect DFV. However, up to 70% of women experiencing Domestic and Family Violence (DFV) go undetected by hospital staff. While routine DFV screening is internationally encouraged, there is still much debate surrounding its implementation. The aim of the study was to determine staff perceptions of barriers and enablers of DFV screening and response. Methods A cross-sectional survey was conducted at a tertiary level public hospital and health service. Health care staff in allied health, maternity and mental health divisions (n = 615) were invited to participate by email and through team meetings. 172 responses were analysed. Results Less than a third of respondents reported routinely asking patients about DFV, with 34.9% reporting they did not have sufficient training to assist with DFV. Increased levels of training were positively correlated with screening practices, preparedness and knowledge. Major barriers were presence of partner and language barriers, while written protocols and supportive work environment were the principal enablers of screening. Conclusion Staff generally believed that routine screening was important and should encompass all forms of abuse. Many felt ill-equipped to ask about or manage disclosure of DFV. More training improves staff capacity for DFV detection and response, and written guidelines should be made available to all staff.